Legal Certainty in Guaranteeing Foreign Investment in Timor Leste to Improve The National Economy - Antonino Pedro Marsal; Eugenia Brandao Da Silva; Carolina da Cruz; Lucinda Quintas (Rechtsnormen: Journal of Law, 2024)
Background: The ASEAN Economic Community (AEC) serves as a platform for economic integration in Southeast Asia, aiming for broader global economic synergy. Its blueprint envisions unrestricted movement of goods, services, capital, and investment across national borders. Investment is critical in enhancing Timor-Leste's national economy. However, achieving this requires an efficient licensing bureaucracy, a conducive investment climate, and government commitment to ensuring legal certainty. Objective: This study aims to analyze the role of legal certainty in attracting foreign investment in Timor-Leste, addressing the challenges posed by the ASEAN Economic Community. Methodology: A normative approach was employed, focusing on legal norms and their role in guaranteeing investment security in Timor-Leste within the AEC framework. Findings: First, the government must establish legal certainty to ensure a secure environment for investors, with consistent implementation of existing laws. Second, the establishment of an arbitration body is essential for swift and transparent business dispute resolution, meeting investor expectations. Third, prioritizing strategic economic sectors can effectively attract foreign investment. Conclusion: Legal certainty plays a pivotal role in attracting investors to Timor-Leste. Transparent dispute resolution through arbitration and promotion of priority sectors significantly enhance the country's appeal to foreign investors.